Recent advances in phase change material based nanoplatforms for cancer therapy. Issue 1 (26th November 2020) - Cao, Changyu; Yang, Nan; Dai, Hanming; Huang, Han; Song, Xuejiao; Zhang, Qi; Dong, Xiaochen
Abstract : The enhanced synergistic effect of cancer combination therapy could be realized with the support of controllable thermal-responsive PCM-based nanoplatforms. Abstract : Cancer has become a severe threat to human life due to its high mortality and metastatic rate. Effective inhibition and killing of cancer cells using chemotherapeutic drugs have been a promising means in clinical cancer therapy. However, the low selectivity, drug-resistance, uncontrollability and serious side effects of chemotherapy significantly limit its further development. There is an urgent need for new treatment strategies to compensate for deficiencies inherent in chemotherapy alone. A growing body of research shows that combined treatment strategies have the potential to overcome this dilemma by achieving significantly enhanced synergistic effects and reduced side effects. Emerging phase change materials (PCMs) create an ideal nanoplatform for cancer combination therapy due to their universal loading properties, stable and temperature-responsive phase transition capability, and excellent natural biocompatibility/biodegradability. The release of therapeutic agents can be precisely controlled through external, non-intrusive stimuli (such as NIR light and ultrasound), avoiding systemic toxicity associated with conventional chemotherapy. Herein, the construction methods and design principles of PCM-based nanoplatforms serving as strict gatekeeper and smart payload delivery systems are discussed in detail. Moreover, the advantages and disadvantages of these nanoplatforms are provided. A suitable discussion and perspective of the remaining challenges and future opportunities for PCM-based nanoplatforms in cancer treatment are also given in conclusion.